Theater of Ipoh cuisine: regeneration in Ipoh Town - Low, Zhi Ling; Ismail, Sumarni; Yusoff, Sarizal Yusman; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, AENSI Publications, 2015)
Food is considered as a primary aspect in our daily life whereby its preparation and consumption as an important element of cultural heritage and a platform for cultural exchange. The unique and exquisite identity of Malaysian’s food is being used as a cultural regeneration strategy to boost the tourism industry while preserving the essence of the local regional cuisine among our local community. Integrating food with architecture is creating a new experience-related space in a city that will promote cultural and social interactions. Ipoh is considered as a hidden gem that house a number of delicacies in our country other than its architecture and natural settings. In fact, Ipoh has its own potential to be promoted as a regional cuisine and culinary centre in Malaysia due to its natural settings surrounded by limestone hills and rivers rich with natural resources. Sadly to say, Ipoh started lost its vibrancy due to the inconsistent urban sprawling with its local cultural context, the local cuisine is not being well-promoted and it’s in danger of being forgotten. There is lacking of architecture platform to showcase the local cultures, history and cuisines that represent Ipoh. Hence, this paper is to explore and develop the idea of merging local food and architecture into a regional cuisine theater as the catalyst of cultural-led regeneration in the intersection point of Ipoh Old Town and New Town. Implication concept of in-between urban space will help to enhance the process of Ipoh Town regeneration to showcase the local cultures while serving as a connecting link for the community, tourists and cultures.